Psychometric Properties of the State-Trait Anxiety Inventory (Form Y) among Malaysian University Students - Seok, Chua Bee; Abd Hamid, Harris Shah; Mutang, Jasmine Adela; Ismail, Rosnah (MDPI, 2018)
Health Ministry statistics showed mental health problems among Malaysian students increased from one in ten individuals in year 2011 to one in five in 2016. Anxiety and depression were cited as the main causes of mental health problems among students in Malaysia. However, an anxiety measure that has been validated for use with Malaysian students is still lacking. Thus, the main objective of the current study is to examine the psychometric proprieties of the State-Trait Anxiety Inventory (Form Y) (STAI), and to assess the suitability of the factorial model in the context of Malaysia. The STAI contains separate scales for measuring state and trait anxiety. A Confirmatory Factor Analysis (CFA) was conducted to test and to compare the two-factor model (State Anxiety and Trait Anxiety) and the four-factor model (State Anxiety Present, State Anxiety Absent, Trait Anxiety Present, and Trait Anxiety Absent) of STAI. In addition, the reliability and validity of the model were also tested. The sample consisted of 341 university students from one of the universities in Kota Kinabalu, Sabah. The results supported a better fit to the data for the four-factor model of STAI. To improve composite reliability and the average variance extracted (AVE) of the constructs, one item was removed from each of the State Anxiety Present factor, Trait Anxiety present factor, and Trait Anxiety Absent factor. Convergent validity for the four-factor model was also improved by the removal of the three items. The findings also suggested that the STAI may have some discriminant validity issues. In the framework of psychology of sustainability and sustainable development, research and intervention regarding this topic should also be enhanced from a primary prevention perspective to improve the quality of life of every human being, fostering wellbeing at all different levels, from individuals to organizations.